Fuzzy PID Control Method for Internet-based Tele-operation Manipulators System - Wei Gao; Miaolei Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Trajectory tracking control problem for internet-based tele-operation system is researched in this paper. The control structure of master and slave tele-operation manipulators adapts bilateral servo control architecture with force deviation feedback. The simulation model of three degrees of freedom (3-DOF) manipulator is presented. In order to ensure the synchronization of positions of the master and slave manipulators, a fuzzy PID control method is proposed. This control algorithm is to adjust the three parameters of PID controller online by fuzzy control method. The contrast simulation experiments of PID and fuzzy PID control methods show that the proposed control method can effectively improve the force and position tracking performance and reduce time delay. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2923